Unbinding Gentility : Women Making Music in the Nineteenth-Century South - Bailey, Candace, 1963- (Book collections on Project MUSE., 2021)
"Southern women of all classes, races, and walks of life practiced music during and after the Civil War. Candace Bailey examines the history of southern women through the lens of these musical pursuits, uncovering the ways that music's transmission, education, circulation, and repertory help us understand its meaning in the women's culture of the time. Bailey pays particular attention to the space between music as an ideal accomplishment-part of how people expected women to perform gentility-and a real practice-what women actually did. At the same time, her ethnographic reading of binder's volumes, letters and diaries, and a wealth of other archival material informs new and vital interpretations of women's place in southern culture. A fascinating collective portrait of women's artistic and personal lives, Unbinding Gentility challenges entrenched assumptions about nineteenth century music and the experiences of the southern women who made it"--